Mechanism of pentoxifylline mediated down-regulation of killer lineage cell functions - R. S. Parhar; P. Ernst; K. Sheth; M. Einspenner; S. Al-Sedairy (Mediators of Inflammation)
The authors reported recently that endotoxaemia mediated elevated levels of tumour necrosis factor (TNF-α) and interleukin-1α (IL-1α) were involved in the pathophysiology of acute heat stroke patients. Pentoxifylline (PTX) is known to modulate neutrophil functions. In the present study the effects of PTX on lipopolysaccharide (LPS) and cytokine induced T-cell and macrophage (ΦM) activation, and on natural killer (NK) cell and lymphokine activated killer (LAK) cell mediated cytotoxicity were examined. Finally, the effect of PTX on the expression of adhesion molecules (LFA-1, Mac-1 and ICAM-1), and cytokine (IL-1α, IL-2, TNF-α, IL-6 and IFN-γ) production and their surface receptor expression in response to LPS activation was investigated. PTX free cultures served as a control. Results revealed that PTX can down-regulate all the above-mentioned immunological parameters in a dosedependent manner. These findings might have far reaching clinical implications.